Analysis of Provincial Export Performance in Türkiye: A Spectral Clustering Approach - Akusta, Emre (Fırat University, 2025)
This study analyzes and clusters Turkiye's 81 provinces based on their export performance. The study uses import, export and net export data for 2023. In addition, exchange rate-adjusted versions of the data were also included to eliminate the effects of exchange rate fluctuations. Spectral clustering method is used to group the export performance of cities. The optimum number of clusters was determined by the Eigen-Gap method. The Silhouette coefficient method was used to evaluate the clustering performance. As a result of the analysis, it was determined that the data set was optimally separated into 3 clusters. Spectral-clustering analysis based on export performance showed that 42% of the provinces are in the "Low", 33% in the "Medium" and 25% in the "High" export performance category. In terms of import performance, 44%, 33%, 33%, and 22% of the provinces are in the "Medium", "High", and "Low" categories, respectively. In terms of net exports, 38, 35% and 27% of the provinces are in the "Low", "Medium" and "High" net export performance categories, respectively. İzmir has the highest net export performance, while İstanbul has the lowest.

Bu çalışma, Türkiye'nin 81 ilini ihracat performanslarına göre analiz etmekte ve kümelendirmektedir. Çalışmada 2023 yılı ithalat, ihracat ve net ihracat verileri kullanılmıştır. Ayrıca, döviz kuru dalgalanmalarının etkilerini ortadan kaldırmak için verilerin döviz kurundan arındırılmış versiyonları da analize dahil edilmiştir. Çalışmada şehirlerin ihracat performanslarını gruplamak için spektral kümeleme yöntemi kullanılmıştır. Son olarak, optimum küme sayısı ise Eigen-Gap yöntemi ile belirlenmiştir. Kümeleme performansını değerlendirmek için siluet katsayısı yöntemi kullanılmıştır. Yapılan analiz sonucunda veri setinin optimal olarak 3 kümeye ayrıldığı tespit edilmiştir. İhracat performansına dayalı spektral-kümeleme analizi, illerin %42'sinin "Düşük", %33'ünün "Orta" ve %25'inin "Yüksek" ihracat performansı kategorisinde yer aldığını göstermiştir. İthalat performansı açısından illerin %44'ü "Orta", %33'ü "Yüksek" ve %22'si "Düşük" ihracat performansı kategorisinde yer almaktadır. Net ihracat açısından ise illerin %38'i "Düşük", %35'i "Orta" ve %27'si "Yüksek" net ihracat performansı kategorisinde yer almaktadır. Analiz sonuçlarına göre, İzmir en yüksek net ihracat performansına sahipken, İstanbul en düşük net ihracat performansına sahip ildir.
Türkiye’de İllerin İhracat Performansının Analizi?: Spektral Kümeleme Yaklaşımı
Keywords: Development Economics - Macro; Kalkınma Ekonomisi - Makro